Kontribusi Usahatani Bunga Pacar Air (Impatiens balsamina Linn) Terhadap Pendapatan Petani (Studi Kasus di Subak Selisihan Kangin, Desa Selat, Kecamatan Klungkung, Kabupaten Klungkung, Provinsi Bali) (Jurnal Agribisnis dan Agrowisata, 2026)
Contribution of Water Girlfriend Flower Farming (Impatiens balsamina Linn) Farmers' Income (Case Study in Selisihan Kangin Subak, Selat Village, Klungkung District, Klungkung Regency, Bali province). Water girlfriend flower plants are plants that originate from South Asia and Southeast Asia but were only introduced to America in the 19th century. Propagation of henna flowers can use seeds. This study aims to calculate farm income and analyze the feasibility of water girlfriend flower farming, and calculate the contribution of water girlfriend flower farming in Subak Selisihan Kangin. The technique of determining the sample using simple random sampling technique. The sample in this study was determined by the slovin formula from a population of 115 farmers to 32 respondents. Data collection was carried out from March 2023 to April 2023 at Selisihan Kangin Subak, Selat Village, Klungkung District, Klungkung Regency, Bali Province. Analysis of the data used to calculate the source of income of farmers is the analysis of farm income, R/C ratio, and contribution. The results showed that the source of income for water girlfriend flower farmers in 2022 was an average income of water girlfriend flower of Rp. 3,862,516/year/respondent with an average arable land area of 0.50 ha from the intercropping system with chili and green mustard commodities, the contribution of water girlfriend flower farming was 15.88% of the total farmer income of Rp. 24,412,521/year, and farming feasibility with an average value of 2.6 which means R/C > 1, means farming is feasible to be cultivated. Suggestions that need to be considered for farmers who have cultivated the water girlfriend flower commodity to continue to maintain their farming because the intercropping cropping pattern of farmers has various types of commodities produced and various incomes from green mustard, chili and rice commodities.
Keywords: water girlfriend flower; farmer's income; feasibility analysis; contribution